Exploring the Feasibility and Effects of a Ketogenic Diet in Patients With CNS Malignancies: A Retrospective Case Series - Panhans, Cristina M.; Gresham, Gillian; Amaral, L. J.; Hu, Jethro (Frontiers in Neuroscience, 2020)
Background: Recently, the ketogenic diet has been proposed as an adjunct treatment for a range of medical conditions including weight loss, diabetes, cancer, and neurodegenerative diseases. Because malignant CNS tumors are highly dependent on glucose, the use of a ketogenic diet as an adjunct therapy is currently being explored. This case series summarizes our experience implementing a ketogenic diet for patients with CNS malignancies. Methods: Patients diagnosed with CNS malignancies following a ketogenic diet were identified between 2015 and 2017. Malignancies included confirmed diagnoses of glioblastoma (GBM), astrocytoma, or oligodendroglioma. With guidance from a registered dietitian, ketone levels, glucose levels, and weight were regularly collected for several patients along with patient-reported symptoms and adverse effects. Interested patients were asked to follow a 3:1 ketogenic diet for 120 days. The ketogenic diet is a high-fat, moderate protein, and very low carbohydrate diet, where patients limited carbohydrate intake to ≤20 g per day. Brain imaging was reviewed. A series of descriptive analyses were conducted. Results: The ketogenic diet was initiated in 12 patients of which 8 patients contributed data on their blood glucose and ketone levels. The majority of patients were male (n = 10) with a median age of 45 (range 32–62). Diagnoses included GBM (n = 6), grade 2/3 astrocytomas (n = 5) and one patient with a grade 2 spinal cord astrocytoma. Ten of the 12 patients were receiving concurrent treatment; two received supportive care only. The majority of patients with evaluable data (n = 8) maintained ketone levels above 0.5 mM for the duration of 120-day period. Ketone levels generally increased from baseline while glucose levels and BMI decreased. Overall, patients reported improved symptoms over the course of the diet. Imaging also suggested improved disease control and reduction in vasogenic edema. Conclusion: Taking advantage of a tumor’s metabolic inflexibility can have a positive impact on patients, particularly those with CNS malignancies. More structured and statistically planned clinical trials are needed to determine the margin of impact of a ketogenic diet.